Control of Rotary Drill Bit to Reduce Vibration Using Input Shaper - Rein Myo, Thu (2018)
Oil and gas industries and operations are popular these days and they have earned huge amount of income. However, the operation needs to invest a lot of money on drilling process such as equipment, labors, maintenance, energy supply, construction and so on. The investment is mainly based on the environmental situation of drilling process. Deep water drilling well costs more than onshore process. On the other hand, the investment of money is increasing because of the incidents occurred during the drilling process. Equipment failure becomes one of the main problems. This is due to the vibration of the drill string. The vibration of the drill string mainly affects the drill bit and as consequences, the penetration rate become slower and the operation becomes less productive. Among four types of vibrations which are axial, lateral, torsional and eccentered vibrations, this paper will be focus mainly on the axial vibrations with the aid of sample drill string model. Moreover, this model will be analyzed and formulated with multi degree of freedom for spring system. The specifications and parameters for the modelling are developed in order to test the sample. The formulated equations will be put into the MATLAB software and results will be analyzed by using the input shaping method to reduce the axial vibration of drill string.